Two different democratic destinies before Latin America - Lynch Gamero, Nicolas Javier (2018)
There exists an erroneous academic and political dilemma, propelled by the right, when characterizing the current course of Latin America as one that sits between democracy and dictatorship, as the only political horizons possible for the continent. On the contrary, the author affirms that this dispute is actually between elite democracies and social democracies. From this point, the author describes the political processes of the last decades in the region and proposes possible democratic horizons.